Amino acids distribution in economical important plants: a review. Issue 2 (July 2019) - Kumar, Vinod; Sharma, Anket; Kohli, Sukhmeen Kaur; Yadav, Poonam; Bali, Shagun; Bakshi, Palak; Parihar, Ripu Daman; Yuan, Huwei; Yan, Daoliang; He, Yi; Wang, Junfeng; Yang, Ying; et al.
Abstract: Amino acids (AAs) are abundantly found in the food plants and their individual concentration is of enormous importance in terms of nutrition. Therefore it is mandatory to explore the food plants for their nutritional importance. This review gives the overview of AA composition in different food plants. However, in most of the studies the complete AA concentration of food plants has not been reported. The data of 142 economical important plant species were collected from Google Scholar, Scopus and Google. Because the techniques applied by various authors, the units of content, and the conditions of analysis were different, in this review paper, for the purpose of statistical analysis the concentrations of AAs were changed into comparative units on Lys content basis, which is the utmost limiting, most variable species specific essential AAs in plants. The average concentration of relative AAs is: Leu > Asp > Glu > Ala > Glu > Arg > Gly > Ile > Ser > Pro > Lys > Thr > Val > His > Phe > Tyr > Cys > Met > Trp. The average relative content of non-essential AAs was recorded maximum, whereas relative content of aromatic AAs was low. The data was statistically analyzed by Pearson's correlation, cluster analysis (CA), heatmap analysis, principal component analysis (PCA) and non-metric multidimensional scaling (NMDS). Among the analyzed plant species, plants of Pentadipandraceae family recorded maximum total relative AAs content, while minimum total relative AAs content was found in Periplocaceae family.